(untitled) (Applied Biological Research, 2020)
Thymus is a primary lymphoid organ and well developed in young animals. Thymus is large and most active during neonatal stage (Zdrojewicz et al., 2016). It is the modulator of activity of other lymphoid organs, and the knowledge of mechanisms that triggers its development, maturation and involution is vital for understanding the activity of whole lymphoid system (Sikora et al., 2002). The information on the morphological studies on thymus gland in puppy is scanty; therefore, the present study was conducted to record the morphological features during neonatal stage.